24.5k views
18 votes
Need help with this

Need help with this-example-1

1 Answer

2 votes

Answer:

See below.

Explanation:

1.

2a + 3 * (1 + 2) = 2a + 9: Yes. Expression is equivalent.


2.

33v = (3 * v) * 11: Yes. Expression is equivalent.


3.

3b - 19 + 2b = 3b + 19 - 2b: No. Both expressions are different answers.


4.

4(3c - 4) = 2(6c - 8): No. expressions are not equivalent.

User Eugene Gordin
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.